ARCHITECTURAL DESIGN QUALITY BETWEEN BIM COLLABORATIVE LOGIC AND TRADITIONAL CAD LOGIC - Khalid Zaouia; Said Mazouz (International Journal of Innovative Technologies in Social Science, 2024)
Building Information Modeling, often referred to as BIM, is considered an essential part of the design and construction process in many countries. The aim of this study is to test the application of this system in relation to traditional computer aide design (CAD) and to characterize the possible contribution of BIM to architectural quality. The analysis model consists of modeling the design process through an exercise proposed to student architects. The proposed solutions were subjected to a detailed statistical analysis in order to characterize the contribution of BIM elements to design quality. The results show that out of five evaluation criteria, four are in favor of BIM, with a percentage of 80%. For the functionality criteria, the results of the BIM approach and those of CAD are reconciled for the remaining 20%. This research confirms that architectural design using BIM tools, even with a low level of collaboration, leads to a higher quality design than the traditional CAD-based approach.